(untitled) - Mike Battcock (Rome, 1998)
This book presents an overview of the fermented fruit and vegetable products of Africa, Asia and Latin America. The bulletin aims to introduce the reader to the vast wealth of knowledge, much of which is indigenous and undocumented and the importance attached to fermented fruits and vegetables in the diet. At the same time it is a practical handbook, allowing those who are interested to reproduce the products.
Keywords: fermentation